Comparison and Analysis of Thermal Calculation Methods for Fan-cooled Permanent Magnet Motor - YANG Jinxia; LI Weiye; ZOU Yulin; WU Jiangquan (Kongzhi Yu Xinxi Jishu)
In order to comparatively analyze the feasibility of different thermal calculation methods on thermal design and engineering application of motor, based on a fan-cooled permanent magnet motor, it analyzed the flow of fan, the fluid field and temperature-rising of motor. Moreover, it calculated the rated air flow of motor fan with analytic method and finite volume method (FVM) and then the achieved velocity distribution of fluid field. On the basis of fluid calculation, it respectively used equivalent thermal path method and FVM to estimate the temperature rising of motor. Through comparing calculation value and practical value, it proved that the two methods had certain reliability. FVM is more suitable for the improvement and optimization of motor design, and thermal model method can be used for subseries motor design and preliminary design evaluation.